RF-DC conversion efficiency improvement for microwave transmission with pulse modulation. Issue 1 (26th March 2019) - Hirakawa, Takashi; Wang, Ce; Shinohara, Naoki
Abstract : Microwave power transfer (MPT) can solve certain types of problems. For example, Internet of Things requires a flexible configuration of sensor networks, which is hindered by wired-charging sensors. This problem can be overcome by MPT techniques. However, the transmission efficiency of MPT is lower than that of wired transmission. This study focuses on the operation of rectifiers having a pulse-modulated input signal. Although a pulse-modulated wave is effective for improving the RF-DC conversion efficiency, the output voltage waves of rectifiers have a high ripple content. Moreover, the harmonic balance method cannot be used to simulate the operation of a pulse-modulated rectifier. To reduce the ripple content, a smoothing capacitor should be connected in parallel to an output load. We investigated the influence of a smoothing capacitor, the general characteristics of rectifiers under pulse-modulated waves, and the effectiveness of using pulse-modulated waves for improving RF-DC conversion efficiency. In conclusion, we reveal a necessary condition of the smoothing capacitor for improvement, demonstrate the effectiveness of pulse modulation, and show that the optimum impedance with a pulse-modulated wave input is an inverse of duty ratio times as compared to that with continuous wave input.